Hospital Cost Efficiency and System Membership - Kathleen Carey (SAGE Publishing, 2003)
Using a recently developed taxonomy of hospital organizations, this paper estimates a stochastic frontier cost function to test for inefficiency differences among system hospitals having common strategic and/or structural characteristics. System hospitals that centralized around physician arrangements and insurance products display the smallest deviations from the least cost locus. This suggests efficiency benefits from organization of physician and insurance activities at the system level, with discretion over the array of service offerings left to individual members. Policymakers should be mindful of potential efficiency gains from hospital consolidations and be aware that common ownership alone may be too general a rubric for evaluating those gains usefully.